Primary hepatic lymphoma of MALT type mimicking hepatic adenoma treated by hepatectomy: a case report and literature review - Wang, Ren-long; Wang, Jia; Li, Yong-sheng; Wang, Yuan; Su, Qiong (Frontiers in Surgery, 2023)
Background Primary hepatic lymphoma (PHL) is a rare malignant tumor. Extranodal marginal zone lymphoma of the mucosa-associated lymphoid tissue (MALT) is an indolent lymphoma occurring at extranodal sites. The stomach is the most common organ affected by MALT lymphoma, whereas liver-related lymphoma is rarely reported. Its atypical clinical presentation often delays the diagnosis. Owing to the rarity of PHL, identifying its optimal treatment still remains a challenge. Herein, we report a case of PHL of the MALT type mimicking hepatic adenoma that was treated by hepatectomy without chemotherapy and review the scarce literature. Our findings suggest that surgery is an alternative approach to cure patients with localized hepatic lymphoma. Case summary A 55-year-old woman was admitted to our hospital because of upper abdominal discomfort, and a liver lesion was detected by computed tomography. She did not have nausea, fever, fatigue, jaundice, weakness, night sweats, or weight loss before admission. And her previous medical history was unremarkable. There were no positive signs on physical examination. Based on her preoperative examination including magnetic resonance imaging, the liver lesion was suspected to be a hepatic adenoma; however, the possibility of it being a malignancy like hepatocellular carcinoma was not excluded. Therefore, a decision of resection of the lesion was made. During the operation, hepatectomy of segment 4b and cholecystectomy were performed. The patient recovered well; however, after postoperative pathological examination, the lesion was diagnosed as a hepatic lymphoma of MALT type. The patient was reluctant to undergo chemotherapy or radiotherapy. At 18-month follow-up, no significant recurrence was observed, indicating that the treatment had a curative effect. Conclusion Notably, primary hepatic lymphoma of MALT type is a rare, low-grade B-cell malignancy. Making an accurate preoperative diagnosis of this disease is usually difficult, and liver biopsy is an appropriate avenue to improve the diagnostic accuracy. In patients with a localized tumor lesion, hepatectomy followed by chemotherapy or radiotherapy should be considered to achieve better outcomes. Although this study describes an unusual type of hepatic lymphoma mimicking a benign tumor, it has its inherent limitations. More clinical studies are required to establish guidelines for the diagnosis and treatment of this rare disease.